موقف القانون السوداني من الوسائل الفنية لقواعد الإسناد: دراسة تحليلية مقارنة - رحمة، جودة إبراهيم محمد النور (مركز بحوث ودراسات دول حوض البحرالأحمر وجامعة البليدة2, 2021)
هدف هذا البحث إلى: التعرف على الوسائل الفنية لقواعد الإسناد، معرفة أسباب ظهور الوسائل الفنية، إبراز تكييف تلك القواعد في ضوء القانون السوداني. يسعى الباحث لاتباع المنهج التاريخي الوصفي التحليلي الاستقرائي. توصل البحث للعديد من النتائج والتوصيات من أهمها: عالج القانون السوداني مسألة التكييف صراحة بأخذه لنظرية بارتان بإخضاع التكييف لقانون القاضي كغيره من قوانين الدول العربية (المادة 10) من قانون المعاملات المدنية السوداني. إن عملية الإحالة كعملية فنية تعني أن قواعد الإسناد في القانون الواجب التطبيق تحيل بدورها الحكم إلى قانون أخر قد يكون هذا القانون هو قانون المحكمة التي حالت في البدء إلى نفس القانون (عملية ارتداد) أو يكون قانون دولة أخرى، هنالك عدد من الدول ترفض الأخذ بالإحالة كالقانون السوداني والمصري والعراقي والإيطالي، عالج القانون السوداني مسألة التفويض بنص صريح وهي المادة 15 من قانون المعاملات.
The importance of this research lies in the increasing multiplicity of private law topics. Therefore, the aim of the research is to: Identify the technical means for the rules of attribution, to know the reasons for the emergence of technical means, to highlight the adaptation of those rules in light of Sudanese law. The researcher seeks to follow the inductive analytical descriptive historical method. The research reached many conclusions and recommendations, the most important of which are: Sudanese law dealt with the issue of adaptation explicitly by adopting Bartan theory by subjecting conditioning to the judge’s law like other laws of Arab countries (Article 10) of the Sudanese Civil Transactions Law. The referral process as a technical process means that the rules of attribution in the applicable law in turn refer the judgment to another law. This law may be the law of the court that initially referred to the same law (apostasy process) or it is the law of another country, and there are a number of countries that refuse to take Referring to the Sudanese, Egyptian, Iraqi and Italian laws, Sudanese law explicitly addressed the issue of delegation, namely Article 15 of the Transactions Law.
Keywords: القوانين والتشريعات -- التكييف القانوني -- تسوية المنازعات -- القانون المدني -- السودان